EMPLOYEES’ PERCEPTION ON ENVIRONMENTAL EDUCATION IN STATE SCHOOLS IN THE MUNICIPALITY OF SÃO GABRIEL-RS - Freitas, Daniele Oliveira; Senna, Ana Júlia Teixeira; Alves, Ricardo Ribeiro (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611706318 Environmental education is an essential tool for the consolidation of a sustainable paradigm.Education is responsible for furnishing information and for promoting the construction ofknowledge. The goal of this paper is to analyze the perception of the employees of ElementaryState Schools, located in the municipality of São Gabriel-RS, towards environmental education intheir workplace. A total of 28 questionnaires were applied at the schools themselves. Through theresults it is possible to ascertain that in School A, all the employees know what environmentalmanagement practices are and they always try to conduct these practices in their households. Onthe other hand, at School B, there is a selective garbage collection system in place, although theschool community is not yet environmentally aware in its entirety.